Dermal Regeneration Template and Staged Skin Grafting for Extirpative Scalp Wound Reconstruction: A 14‐Year Experience. (16th February 2021) - Maus, Jacob C.; Hemal, Kshipra; Khan, Mija; Calder, Bennett W.; Marks, Malcolm W.; Defranzo, Anthony J.; Pestana, Ivo Alexander
Abstract : Objective: Dermal regeneration template and staged split‐thickness skin grafting may mitigate the need for flap coverage of postoncologic scalp defects. This technique has been studied previously in small case series. We examine the effect of risk factors, surgical technique, irradiation, and dressing modalities on reconstructive outcomes in a highly comorbid patient cohort. Study Design: Retrospective review. Setting: Academic medical center. Methods: Full‐ and partial‐thickness extirpative scalp wounds reconstructed with dermal regeneration template and staged skin grafting were reviewed over a 14‐year period. Stage 1 consisted of template application following burr craniectomy in cases lacking periosteum. Stage 2 consisted of skin grafting. Negative pressure wound therapy (NPWT) was variably used to support adherence. Results: In total, 102 patients were analyzed (average age 74, mean follow‐up 18 months). Eighty‐one percent were American Society of Anesthesiologists class 3 or 4. Defect size averaged 56 cm 2 . Average skin graft take was 94.5% in full‐thickness wounds. Seven patients failed this method. Preoperative scalp irradiation was associated with major complication and delayed graft healing. Comorbidities, wound size, and burring were not associated with complication. Patients were more likely to heal with NPWT compared to bolster (hazard ratio, 1.67; 95% CI 1.01‐2.77; P =. 046). Time between stages was 6.6 days shorter when NPWT was applied ( P <. 001). Conclusion: Dermal template and staged skin grafting is a reliable option for postcancer scalp reconstruction in poor flap candidates. Radiotherapy is associated with adverse outcomes. Negative pressure wound therapy simplifies postoperative wound care regimens and may accelerate healing.